The Effectiveness of Football Learning Through the Playing K Approach to Motor Ability for Riau Sports High School Students: Efektivitas Pembelajaran Sepakbola Melalui Pendekatan Bermain K Terhadap Motor Ability Bagi Siswa Sman Olahraga Riau - Ricky Fernando; Zulrafli Zulrafli; Sasmarianto Sasmarianto (Jurnal Olahraga dan Kesehatan (ORKES), 2022)
Football learning has a complex movement that is very skillful (Sartono et al., 2020). The skills taught are not just playing skills, but more on the actual application of the game in football on the field. The influence of physical education subject teachers also plays a very important role in the success of football learning (Effendi & Rhamadhansyah, 2017). It must also provide changes to all components that exist in the structure of football movement. In addition, the keywords of soccer learning have three important aspects in learning, namely cognitive, affective, and psychomotor (Nururi & Sulaiman, 2015; Taufik & Gaos, 2019). This study aims to improve the motor ability of Riau Sports High School students in learning football. The method used in this research is the experimental method. The results showed that the play approach was better than the technical approach. So it can be concluded that the play approach is considered more effective and can be applied inlearning football in schools.